2006
DOI: 10.1177/0265407506068260
|View full text |Cite
|
Sign up to set email alerts
|

Divided we fall: Children's friendships and peer victimization

Abstract: This study examined the contributions of peer acceptance and friendship (i.e., number and quality) on children being relationally or overtly peer victimized. Fifth-and sixth-grade children (N= 207, 92 boys) provided self-and peer-reports of victimization, friendship, and peer acceptance. General peer acceptance and high-quality friendships uniquely predicted both overt and relational victimization. Fall victimization did not predict spring friendship quality; however, fall friendship quality did predict spring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 34 publications
6
51
0
2
Order By: Relevance
“…More important, friendship quality was found to be especially important for adolescents' adjustment when overall peer acceptance and number of friends are low (Waldrip et al, 2008). Furthermore, high-quality reciprocated friendships at school also act as a buffer against overt victimization, when peer acceptance is low (Malcolm et al, 2006). According to Malcolm and colleagues (2006), a high-quality friend can be defined as someone who provides companionship, intimacy, and support.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
See 1 more Smart Citation
“…More important, friendship quality was found to be especially important for adolescents' adjustment when overall peer acceptance and number of friends are low (Waldrip et al, 2008). Furthermore, high-quality reciprocated friendships at school also act as a buffer against overt victimization, when peer acceptance is low (Malcolm et al, 2006). According to Malcolm and colleagues (2006), a high-quality friend can be defined as someone who provides companionship, intimacy, and support.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Fifth, none of the previous studies took possible gender differences into account. Previous research in elementary and secondary school revealed that in the typically developing population, friendship quality is rated higher among girls than among boys (e.g., Berndt & McCandless, 2009;Bowker, 2004;Malcolm et al, 2006). So far, nothing is known about gender differences in friendship quality for the SEN population.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Friendship quality was assessed by an instrument developed by Malcolm, Jensen-Campbell, Rex-Lear, and Waldrip (2006) which assesses friendship quality of best friendships. Students were asked to answer four questions about the quality of the relation with each nominated friend.…”
Section: Friendship Qualitymentioning
confidence: 99%
“…Here researchers have attended to precursors of peer victimization such as lower social preference and peer acceptance (Schwartz et al 1999), outcomes such as social withdrawal and loneliness (Boulton and Underwood 1992), and intervening mechanisms such as friendship quality that link victimization to psychological adjustment (Malcolm et al 2006). Less well known is whether peer victimization experiences at school are associated with other aspects of adolescents' social lives such as parent-adolescent interactions at home.…”
mentioning
confidence: 99%